2020
DOI: 10.3389/fonc.2020.00381
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Resection for Metastasis of Hepatocellular Carcinoma Recurring After Liver Transplant: An Italian Multicenter Experience

Abstract: rejection. The 1 and 5 year cumulative probability of OS from recurrence were 100 and 43% (95%CI 12-74), respectively, with a median OS of 51 months (95%CI 24-78). Conclusion:Selected patients with isolated pulmonary HCC-recurrence after LT and with preserved hepatic function showed that a pulmonary metastasectomy could be efficacious in managing a PM-HCC and could give an opportunity for long-term survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 31 publications
0
10
0
1
Order By: Relevance
“…Amongst the subtypes of liver cancer, hepatocellular carcinoma (HCC) has the highest incidence and accounts for >80% of primary liver cancer types (3). Currently, there are various therapeutic approaches available for HCC, including surgical resection, cryotherapy, laser therapy and interventional surgery; however, due to the highly invasive and metastatic nature of HCC, the median survival time of patients with advanced HCC is only 3-6 months, and the 5-year survival rate remains at 12.5% (4,5). Therefore, the pathological mechanisms of HCC at the molecular level should be further investigated to determine effective treatment targets for HCC.…”
Section: Introductionmentioning
confidence: 99%
“…Amongst the subtypes of liver cancer, hepatocellular carcinoma (HCC) has the highest incidence and accounts for >80% of primary liver cancer types (3). Currently, there are various therapeutic approaches available for HCC, including surgical resection, cryotherapy, laser therapy and interventional surgery; however, due to the highly invasive and metastatic nature of HCC, the median survival time of patients with advanced HCC is only 3-6 months, and the 5-year survival rate remains at 12.5% (4,5). Therefore, the pathological mechanisms of HCC at the molecular level should be further investigated to determine effective treatment targets for HCC.…”
Section: Introductionmentioning
confidence: 99%
“…Lung is the most common site of recurrence, probably owing to proximity to the liver at the time of hepatectomy, and the lymphatic drainage [45] . In our study, we also observed that lungs were the most frequent site of HCC recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…In a large series of pulmonary metastatectomy cases post LT, Hwang et al [48] showed that those patients who were selected for surgery based on the feasibility of complete resection and sufficient pulmonary function after surgery, the 5-year survival rate was significantly better. A large Italian multicenter study [45] found that pulmonary metastatectomy with a low complication rate was feasible in patients who were judged operable when they developed pulmonary metastasis as the first metastasis after LT for HCC. One year, 3-yr, and 5-yr cumulative overall survival rates of 100%, 66%, and 43%, respectively, were reported in this study, with a median OS of 51 months.…”
Section: Discussionmentioning
confidence: 99%
“…V jiné práci u pacientů pouze se systémovou léčbou sorafenib-lenvatinib byl medián přežití 19,5 měsíce [38]. Italská multicentrická studie uvádí u pacientů, kteří podstoupili resekci plicních metastáz, pravděpodobnost 5letého přežívání 43 % a medián přežívání 51 měsíců [39].…”
Section: Transplantace Jater Pro Rekurenci Hcc Po Resekci Nebo Ablaciunclassified